2017
DOI: 10.1080/2162402x.2017.1373235
|View full text |Cite
|
Sign up to set email alerts
|

The “don't eat me” signal CD47 is a novel diagnostic biomarker and potential therapeutic target for diffuse malignant mesothelioma

Abstract: Diffuse malignant mesothelioma (DMM) is one of the prognostically most discouraging cancers with median survivals of only 12–22 months. Due to its insidious onset and delayed detection, DMM is often at an advanced stage at diagnosis and is considered incurable. Combined chemo- and radiotherapy followed by surgery only marginally affect outcome at the cost of significant morbidity. Because of the long time period between exposure to asbestos and disease onset, the incidence of DMM is still rising and predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…CD47 can be expressed on many healthy cells in mice and humans and is highly expressed on a variety of CSCs, including both hematopoietic and solid tumors (145). Expression of CD47 in tumor cells avoid their recognition and elimination by macrophages, dendritic cells, and T cells and induces epithelialmesenchymal transition (EMT) through modulation of Ncadherin and E-cadherin (146).…”
Section: Impaired Dcs Recruitment: Ccl4 Inhibitionmentioning
confidence: 99%
“…CD47 can be expressed on many healthy cells in mice and humans and is highly expressed on a variety of CSCs, including both hematopoietic and solid tumors (145). Expression of CD47 in tumor cells avoid their recognition and elimination by macrophages, dendritic cells, and T cells and induces epithelialmesenchymal transition (EMT) through modulation of Ncadherin and E-cadherin (146).…”
Section: Impaired Dcs Recruitment: Ccl4 Inhibitionmentioning
confidence: 99%
“…Numbers of stromal macrophages were positively correlated to the number of stromal Tregs ( R = 0.41, p = 0.002), suggesting that macrophages stimulate and recruit CD4+ cells by affecting the adaptive immune response [ 15 , 21 ]. Schürch et al found heavy infiltration of M2 macrophages in all 40 MPM analyzed [ 22 ]. Table 2 summarizes the extent of macrophage infiltration found in these studies.…”
Section: Macrophagesmentioning
confidence: 99%
“…An important function of CD47 is its role as a marker of self and a “don’t eat me” signal that inhibits phagocytosis by binding to signal regulatory protein α (SIRPα) on macrophages (Figure 3 C) ( 253 255 ). Overexpression of CD47 has been reported on numerous solid and hematological human cancers, and blocking CD47 promotes macrophage activation, enhances tumor cell phagocytosis and prolongs survival in murine cancer models ( 256 264 ). Importantly, CD47 is overexpressed on AML LSCs and further upregulated during their mobilization.…”
Section: Antibodies That Activate Antitumoral Innate Immunity: Tams Amentioning
confidence: 99%